A high-speed X-ray Radiography Setup for in-situ Electron Beam Powder Bed Fusion at PETRA III - Bidola, Pidassa M.; Abreu-Faria, Guilherme; Klingenberg, Johannes; Brehling, Jens; Burmester, Hilmar; Tietze, Ursula; Krywka, Christina; Staron, Peter; Schwebke, Bernd; Lottermoser, Lars; Lindwall, Greta; Ioannidou, Chrysoula; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
A high-energy white synchrotron X-ray beam enables penetration of relatively thick and highly absorbing samples. At the P61A White Beam Engineering Materials Science Beamline, operated by Helmholtz-Zentrum Hereon at the PETRA III ring of the Deutsches Elektronen-Synchrotron (DESY), a tailored X-ray radiography system has been developed to perform in-situ X-ray imaging experiments at high temporal resolution, taking advantage of the unprecedented X-ray beam flux delivered by ten successive damping wigglers. The imaging system is equipped with an ultrahigh-speed camera (Phantom v2640) enabling acquisition rates up to 25 kHz at maximal resolution and binned mode. The camera is coupled with optical magnification (5x, 10x) and focusing lenses to enable imaging with a pixel size of 1,35 micrometre. The scintillator screens are housed in a special nitrogen gas cooling environment to withstand the heat load induced by the beam, allowing spatial resolution to be optimized down to few micrometres. We present the current state of the system development, implementation and first results of in situ investigations, especially of the electron beam powder bed fusion (PBF-EB) process, where the details of the mechanism of crack and pore formation during processing of different powder materials, e.g. steels and Ni-based alloys, is not yet known.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Electron beam Powder Bed Fusion; High-speed X-ray radiography; In-situ X-ray imaging

Electron-optical in-situ crack monitoring during electron beam powder bed fusion of the Ni-Base superalloy CMSX-4 - Bäreis, Johannes; Semjatov, Nick; Renner, Jakob; Ye, Jihui; Fu, Zongwen; Körner, Carolin (Progress in Additive Manufacturing, 2022)
Electron beam powder bed fusion (PBF-EB) of Ni-base superalloys such as CMSX-4 is a demanding process. Using conventional PBF-EB machines, process observation is done by mounting optical camera systems on viewing windows at the top of the build chamber. However, the concomitant metallization blocks optical observation methods with increasing build time. Therefore, build quality evaluation is normally done after the process utilizing visual inspection or subsequent metallurgical analysis. In this work, CMSX-4 is processed using a freely programmable PBF-EB machine with an electron optical (ELO) imaging system. It consists of a four-segment ELO detector and in-house developed imaging software. The ELO system works reliably for almost 30 h of build time and allows a layerwise monitoring of the build area. A comparison of in-situ ELO monitoring and the sample surfaces shows remarkable accordance. Furthermore, ELO imaging is applied to exemplarily document surface cracking over long build times. Therefore, the present study successfully demonstrates the application of ELO imaging for improved process control under the demanding test conditions of Ni-base superalloys.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Additive manufacturing; CMSX-4; Electron-beam powder bed fusion; ELO-imaging; In-situ process monitoring

In-situ synchrotron X-ray analysis of metal Additive Manufacturing: Current state, opportunities and challenges - Ioannidou, Chrysoula; König, Hans Henrik; Semjatov, Nick; Ackelid, Ulf; Staron, Peter; Körner, Carolin; Hedström, Peter; Lindwall, Greta (Materials and Design, 2022)
Additive Manufacturing (AM) is becoming an important technology for manufacturing of metallic materials. Laser-Powder Bed Fusion (L-PBF), Electron beam-Powder Bed Fusion (E-PBF) and Directed Energy Deposition (DED) have attracted significant interest from both the scientific community and the industry since these technologies offer great manufacturing opportunities for niche applications and complex geometries. Understanding the physics behind the complex and dynamic phenomena occurring during these processes is essential for overcoming the barriers that constrain the metal AM development. In-situ synchrotron X-ray characterization is suitable for investigating the microstructure evolution during processing and provides new profound insights. Here, we provide an overview of the research on metal PBF and DED using in-situ synchrotron X-ray imaging, diffraction and small-angle scattering, highlighting the state of the art, the instrumentation, the challenges and the gaps in knowledge that need to be filled. We aim at presenting a scientific roadmap for in-situ synchrotron analysis of metal PBF and DED where future challenges in instrumentation such as the development of experimental stations, sample environments and detectors as well as the need for further application oriented research are included.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Directed energy deposition; In-situ studies; Metal additive manufacturing; Powder bed fusion; Synchrotron X-ray characterization

MiniMelt: An instrument for real-time tracking of electron beam additive manufacturing using synchrotron x-ray techniques - König, Hans Henrik; Semjatov, Nick; Spartacus, Gabriel; Bidola, Pidassa; Ioannidou, Chrysoula; Ye, Jihui; Renner, Jakob; Lienert, Ulrich; Abreu-Faria, Guilherme; Wahlmann, Benjamin; Wildheim, Martin; Ackelid, Ulf; et al. (Review of Scientific Instruments, 2023)
The development of a sample environment for in situ x-ray characterization during metal Electron Beam Powder Bed Fusion (PBF-EB), called MiniMelt, is presented. The design considerations, the features of the equipment, and its implementation at the synchrotron facility PETRA III at Deutsches Elektronen-Synchrotron, Hamburg, Germany, are described. The equipment is based on the commercially available Freemelt ONE PBF-EB system but has been customized with a unique process chamber to enable real-time synchrotron measurements during the additive manufacturing process. Furthermore, a new unconfined powder bed design to replicate the conditions of the full-scale PBF-EB process is introduced. The first radiography (15 kHz) and diffraction (1 kHz) measurements of PBF-EB with a hot-work tool steel and a Ni-base superalloy, as well as bulk metal melting with the CMSX-4 alloy, using the sample environment are presented. MiniMelt enables time-resolved investigations of the dynamic phenomena taking place during multi-layer PBF-EB, facilitating process understanding and development of advanced process strategies and materials for PBF-EB.<br
CRIS-Team Scopus Importer:2023-12-15

Multiple interaction electron beam powder bed fusion for controlling melt pool dynamics and improving surface quality - Semjatov, Nick; Wahlmann, Benjamin; Körner, Carolin (Additive Manufacturing, 2024)
Low surface quality of fabricated parts and long processing times are two commonly stated reasons against a more wide-spread adoption of electron beam powder bed fusion (PBF-EB) as a commercially viable manufacturing technique. Aside from the large particle size distribution (45–150 µm) of processed powders, the surface roughness, limited structural resolution and process instabilities are attributed to unwanted dynamics of the melt pool, like spattering, balling, evaporation and melt pool displacement. As a result, a contouring step using slow but stable melting parameters is usually added to the process to improve surface quality, leading to increased processing times. In this study, we demonstrate how the surface quality can be improved by supplying the energy for melt pool formation over multiple, timely separated interactions. To investigate the effect of this multiple interaction processing (MIP), series of single line melt structures with increasing number of interactions were fabricated, characterized and corresponding thermal diffusion simulations performed. The experimental results show how MIP allows to lower surface roughness of melted structures through a reduction of spattering, balling and melt pool displacement during processing, while our simulation model identifies these benefits to be caused by a significant reduction in surface temperature and thus evaporation, with increasing number of interactions for melt pool formation. Our model further demonstrates, how a relatively simple, computationally inexpensive and thus scalable thermal diffusion model is capable of providing valuable information about thermal conditions during melt pool formation. Lastly, we introduce a few simple equations to calculate appropriate MIP parameters for any kind of scan strategy.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Electron beam powder bed fusion; Evaporation; Melt pool dynamics; Surface roughness; Thermal diffusion simulation

Revealing the Mechanisms of Smoke during Electron Beam–Powder Bed Fusion by High-Speed Synchrotron Radiography - Ye, Jihui; Semjatov, Nick; Bidola, Pidassa; Lindwall, Greta; Körner, Carolin (Journal of Manufacturing and Materials Processing, 2024)
Electron beam–powder bed fusion (PBF-EB) is an additive manufacturing process that utilizes an electron beam as the heat source to enable material fusion. However, the use of a charge-carrying heat source can sometimes result in sudden powder explosions, usually referred to as “Smoke”, which can lead to process instability or termination. This experimental study investigated the initiation and propagation of Smoke using in situ high-speed synchrotron radiography. The results reveal two key mechanisms for Smoke evolution. In the first step, the beam–powder bed interaction creates electrically isolated particles in the atmosphere. Subsequently, these isolated particles get charged either by direct irradiation by the beam or indirectly by back-scattered electrons. These particles are accelerated by electric repulsion, and new particles in the atmosphere are produced when they impinge on the powder bed. This is the onset of the avalanche process known as Smoke. Based on this understanding, the dependence of Smoke on process parameters such as beam returning time, beam diameter, etc., can be rationalized.
CRIS-Team Scopus Importer:2024-07-12
Keywords: electron beam–powder bed fusion (PBF-EB); high-speed synchrotron; in situ; radiography; smoke effect